Phylogenetic analysis of the E2 gene of classical swine fever viruses from Lao PDR. - Blacksell, S; Khounsy, S; Boyle, D; Greiser-Wilke, I; Gleeson, L; Westbury, H; Mackenzie, J (2004)
The E2 genes of 21 classical swine fever viruses (CSFV) were genetically characterized and compared with reference CSF viruses. The viruses originated from CSF outbreaks that occurred in the Lao People's Democratic Republic (Lao PDR) during 1997 though to 1999. All viruses characterized belonged to genogroup 2 and were members of subgroups 2.1 and 2.2. Results demonstrated a geographic delineation between subgroups 2.1 that was only found in the North-Central region, and subgroup 2.2 that was mostly found in the South-Central regions of Lao PDR. Although it was not possible to determine the origin of these viruses, it is probable that they may have been introduced to Lao PDR following cross-border trade. Alternatively, they have evolved independently of other viruses in the region.